International Monetary Fund Administrative Tribunal Reports, Volume III, 2003-2004. (International Monetary Fund, 2009)
This paper provides an analysis of the Tribunal's jurisprudence for the period is provided in an introductory chapter, "Developments in the Jurisprudence of the International Monetary Fund Administrative Tribunal: 2003-2004." The standard of review, understood as describing the relationship between the Administrative Tribunal and the decision maker responsible for the contested decision, represents the degree of deference accorded by the Tribunal to the decision maker's judgment. The standard of review is designed to set limits on the improper exercise of power and represents a legal presumption about where the risk of an erroneous judgment should lie. In defining the Tribunal's standard of review in disability retirement cases, the Tribunal clarified its relationship to the channels of administrative review as follows. The Tribunal confirmed its authority to make both findings of fact and conclusions of law, and therefore to review de novo the legality of an administrative act of the IMF.